Innovative developments for long‐term mammalian pest control. Issue 3 (4th October 2013) - Blackie, Helen M; MacKay, Jamie W.B; Allen, Will J; Smith, Des H. V; Barrett, Brent; Whyte, Belinda I; Murphy, Elaine C; Ross, James; Shapiro, Lee; Ogilvie, Shaun; Sam, Shona; MacMorran, Duncan; et al.
Abstract BACKGROUND Invasive mammalian pests have inflicted substantial environmental and economic damage on a worldwide scale. RESULTS Over the last 30 years there has been minimal innovation in the development of new control tools. The development of new vertebrate pesticides, for example, has been largely restricted due to the costly and time‐consuming processes associated with testing and registration. CONCLUSION In this article we discuss recent progress and trends in a number of areas of research aimed to achieve long‐term population suppression or eradication of mammalian pest species. The examples discussed here are emerging from research being conducted in New Zealand, where invasive mammalian pests are one of the greatest threats facing the national environment and economy. © 2013 Society of Chemical Industry